2021
DOI: 10.1111/joim.13266
|View full text |Cite
|
Sign up to set email alerts
|

Acrodermatitis chronica atrophicans: clinical and microbiological characteristics of a cohort of 693 Slovenian patients

Abstract: Background. Information on large groups of patients with acrodermatitis chronica atrophicans (ACA) is limited.Methods. We assessed clinical and microbiological characteristics of patients with ACA diagnosed at a single medical centre and compared findings in periods 1991-2004 vs. 2005-2018. The cohort is representative of Slovenian ACA patients.Results. We assessed 693 patients: 461 females and 232 males, with median age of 64 years. Median duration of ACA before diagnosis was 12 months. In all but 2 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…It starts with reddish-blue discoloration and swelling of the skin (an inflammatory phase), which slowly enlarges and, if untreated, is followed by atrophic changes several months to years later. For some patients, ACA was known to have been preceded by an earlier manifestation of Lyme disease, such as erythema Risk depends on the geographic area; the most common co-infection is tick-borne encephalitis migrans (18). The apparent explanation for the absence of these manifestations in the United States is that these skin infections are principally caused by B. afzelii (Table 3).…”
mentioning
confidence: 99%
“…It starts with reddish-blue discoloration and swelling of the skin (an inflammatory phase), which slowly enlarges and, if untreated, is followed by atrophic changes several months to years later. For some patients, ACA was known to have been preceded by an earlier manifestation of Lyme disease, such as erythema Risk depends on the geographic area; the most common co-infection is tick-borne encephalitis migrans (18). The apparent explanation for the absence of these manifestations in the United States is that these skin infections are principally caused by B. afzelii (Table 3).…”
mentioning
confidence: 99%
“…For example, although ACA is described as the most common late disease manifestation (Mullegger, 2004; Steere et al., 2016), it is rare in the US and merely endemic in certain parts of Europe (DiCaudo et al., 1994). B. afzelii has been found to be most abundant in biopsied patients with ACA (Brandt et al., 2015; Ogrinc et al., 2021; Rijpkema et al., 1997), but the exact prevalence of B. afzelii is not known in Türkiye. In this study, we could only identify one reported case of ACA.…”
Section: Discussionmentioning
confidence: 99%
“…131 Some 21%-64% of patients with ACA have a polyneuropathy, which is distal-predominant, symmetric or asymmetric, and primarily sensory. [132][133][134][135] This neuropathy is the only manifestation of neuroborreliosis unassociated with meningitis. Nerve biopsies in neuroborreliosis-related neuropathies reveal mononuclear perivascular inflammation in the epineurium, perineurium, and endoneurium.…”
Section: Neuroborreliosismentioning
confidence: 99%
“…In Europe, 1% of patients develop a late cutaneous manifestation: acrodermatitis chronica atrophicans (ACA) 131 . Some 21%–64% of patients with ACA have a polyneuropathy, which is distal‐predominant, symmetric or asymmetric, and primarily sensory 132–135 . This neuropathy is the only manifestation of neuroborreliosis unassociated with meningitis.…”
Section: Literature Review Of Primary and Secondary Perineuritismentioning
confidence: 99%